How does economic growth affect the well-being in Asia? - Varith Pipitpojanakarn (2018)
© Serials Publications Pvt. Ltd. Investigation is made on the relationship between growth in economic sectors and well-being in Asia, using quantile regression model. Due to the limitation of data set, we thus propose introducing entropy estimation to quantile regression model. The simulation study is also conducted to show the performance and accuracy of the entropy estimation. We compare the entropy estimation with the conventional estimations and find that the entropy estimation outperform the conventional estimation when the data set is overly small. The application results also show that there exists the effect of economic growth on the well-being in some economic sectors.